Effect of the COVID-19 pandemic on patients with inherited neuromuscular disorders - Moreno, Cristiane Araujo Martins; Camelo, Clara Gontijo; Sampaio, Pedro Henrique Marte de Arruda; Fonseca, Alulin Tácio Quadros Santos Monteiro; Estephan, Eduardo de Paula; Silva, André Macedo Serafim; Pirola, Renann Nunes; Silva, Luiz Henrique Libardi; Lima, Karlla Danielle Ferreira; Albuquerque, Marco Antônio Veloso de; Camelo, Antonio Edvan, Filho; Marques, Marcos Vinícius Oliveira; Yanagiura, Mario Teruo; Cavalcante, Wagner Cid Palmeira; Matsui, Ciro, Junior; Isihi, Lucas Michielon de Augusto; Mendonça, Rodrigo Holanda; Pouza, Ana Flávia Pincerno; Carvalho, Mary Souza de; Reed, Umbertina Conti; Zanoteli, Edmar (Arquivos de Neuro-Psiquiatria, 2022)
Background The COVID-19 pandemic has brought substantial challenges for current practices in treating hereditary neuromuscular disorders (hNMDs). However, this infection has not been the only concern for these patients. Social distancing has compromised multidisciplinary assistance and physical activity, and has brought about several mental health issues. We presented a follow-up on 363 patients with hNMDs at a Brazilian tertiary center during the peak of the COVID-19 pandemic. Objective We aimed to show the frequency and severity of SARS-CoV-2 infection among hNMD patients and to demonstrate the effects of the pandemic on life habits, disease progression and multidisciplinary supportive care status. Methods Three hundred and sixty-three patients (58% male and 42% female) were followed for three months through three teleconsultations during the peak of the COVID-19 pandemic in Brazil. Results There were decreases in the numbers of patients who underwent physical, respiratory and speech therapies. For several patients, their appetite (33%) and sleep habits (25%) changed. Physical exercises and therapies were interrupted for most of the patients. They reported new onset/worsening of fatigue (17%), pain (17%), contractions (14%) and scoliosis (7%). Irritability and sleep, weight and appetite changes, and especially diminished appetite and weight loss, were more frequent in the group that reported disease worsening. There was a low COVID-19 contamination rate (0.8%), and all infected patients had a mild presentation. Conclusion The isolation by itself was protective from a COVID-19 infection perspective. However, this isolation might also trigger a complex scenario with life habit changes that are associated with an unfavorable course for the NMD.
Keywords: Neuromuscular Diseases; COVID-19; Social Isolation; Consequence Analysis